2020
DOI: 10.1111/itor.12768
|View full text |Cite
|
Sign up to set email alerts
|

Whether a retailer should enter an e‐commerce platform taking into account consumer returns

Abstract: Considering consumers are increasingly shopping online nowadays and the online sales market is dominated by e‐commerce giants, traditional retailers need to choose whether to enter e‐commerce platforms. Moreover, traditional retailers need to determine whether to offer offline return services considering online return services are very popular. To address these challenges, we explore a retailer's optimal offline return strategy and channel choice of whether or not to enter a platform in the contexts of symmetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 62 publications
0
27
0
Order By: Relevance
“…Such a sales and return model is used extensively in JD (not self-managed), Amazon (FBM), and Pinduoduo. At the same time, the operational model is in line with the operational framework of existing research [32,69,70]. e model structure is shown in Figure 1.…”
Section: Model Descriptionmentioning
confidence: 94%
See 2 more Smart Citations
“…Such a sales and return model is used extensively in JD (not self-managed), Amazon (FBM), and Pinduoduo. At the same time, the operational model is in line with the operational framework of existing research [32,69,70]. e model structure is shown in Figure 1.…”
Section: Model Descriptionmentioning
confidence: 94%
“…For example, Ma et al [16] found the extent to which return policies affect pricing and profits in relation to retailers' unit purchase costs and market return rates. Cao et al [32] accounted for the channel choice of whether retailers should enter e-platforms and found that the choice mainly depends on the e-platform's annual service fee. From the above literature, few scholars have considered consumer returns in ESC.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Both above studies specify the strategic role of platform selling in eliminating the double marginalization effect, which always occurs under the conventional reselling model. Cao et al [25] examine the dilemma faced by firms who sell new and remanufactured products offline that need to consider whether to enter ecommerce platforms considering that more and more consumers are shopping online on e-commerce platforms rather than shopping offline. Yan et al [26] investigate whether and when the manufacturer should introduce the platform selling in addition to the reselling channel, they also study these problems by incorporating online spillover.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Besides a traditional retail channel where the retailers resell manufacturers' products to consumers, an increasing number of retailers are introducing third-party marketplaces (3P marketplaces) for third-party sellers (3P sellers) to sell their products directly to consumers (Rochet and Tirole, 2006;Cao et al, 2019Cao et al, , 2020. For example, the retailer Newegg.com in the United States, JD.com in China, Flipkart in India, Darty in France, and Bol.com in the Netherlands all not only operate a traditional retail channel but also provide a 3P marketplace to the 3P sellers.…”
Section: Introductionmentioning
confidence: 99%